Syneresis‐Driven Self‐Refilling Printing of Geometry/Component‐Controlled Nano/Microstructures - Kota Shiba; Kayoko Saito; Kosuke Minami; Shunto Arai; Genki Yoshikawa; Luyi Sun; Mizuki Tenjimbayashi (Advanced Science)
Abstract Nano/microfabrication is of fundamental importance both in scientific and industrial situations. There are, therefore, many attempts at realizing easier, quicker, and more precise fabrication of various structures; however, achieving this aim without a bulky and costly setup is still challenging. Here, we introduce a facile and versatile means of printing an ordered structure consisting of nanoscale stripes and more complicated geometries including pillars and wavy form with a lateral resolution of single micrometers. To this end, we prepare a polydimethylsiloxane (PDMS) slab with an oxygen plasma‐induced wrinkled surface where liquid PDMS exudes by syneresis. Since this liquid PDMS is automatically loaded, the printing is repeatable without inking. A substrate moderately wettable to the liquid PDMS as well as amount/property‐controlled syneresis is primarily important for the creation of well‐defined structures. Precisely controlling these conditions will make this method universally applicable to diverse substrates and liquids including suspensions.